Analysis of User Satisfaction and Preferences in Choosing a Digital Game Platform (Study Case: Steam vs Epic Games Store) - Muhammad Nabil; Dhani Ariatmanto (Universitas Islam Raden Rahmat, Malang, 2025)
In the digital era, the gaming industry has expanded rapidly, influencing social, cultural, and economic aspects. This study examines user satisfaction and preferences between Steam and Epic Games Store using the End User Computing Satisfaction (EUCS) model. A quantitative approach with descriptive and explanatory methods was employed. The study aims to identify which technical factors most influence user satisfaction and preferences between Steam and Epic Games Store. Using the EUCS model, the research will provide insights for developers to enhance user experience and inform strategies for improving digital gaming platforms. The findings will contribute to understanding technical drivers of user behavior and offer recommendations for creating user-centered design strategies in the competitive gaming market. Data analysis reveals that Steam holds a significant advantage in Content, Ease of Use, and Timeliness, leading to higher satisfaction. Steam offers a broader game selection, better community features, and a more functional interface than Epic Games Store. Statistical tests confirm Steam’s superiority. The study concludes that users prefer platforms with richer content, better experiences, and more efficient update systems, providing strategic insights for platform developers to improve competitiveness and user satisfaction.